2016
DOI: 10.1038/bonekey.2016.70
|View full text |Cite
|
Sign up to set email alerts
|

Periosteum mechanobiology and mechanistic insights for regenerative medicine

Abstract: Periosteum is a smart mechanobiological material that serves as a habitat and delivery vehicle for stem cells as well as biological factors that modulate tissue genesis and healing. Periosteum's remarkable regenerative capacity has been harnessed clinically for over two hundred years. Scientific studies over the past decade have begun to decipher the mechanobiology of periosteum, which has a significant role in its regenerative capacity. This integrative review outlines recent mechanobiological insights that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 59 publications
(112 reference statements)
0
15
0
Order By: Relevance
“…A great impetus exists for elucidation of periosteum mechanobiology in the context of regenerative medicine , . A number of in vivo preclinical studies have shown PDCs to be comparable or superior to bone marrow stem cells for bone healing and regeneration , .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A great impetus exists for elucidation of periosteum mechanobiology in the context of regenerative medicine , . A number of in vivo preclinical studies have shown PDCs to be comparable or superior to bone marrow stem cells for bone healing and regeneration , .…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for the choice of the ovine model was twofold. First, we aimed to build on our previous body of work using the ovine model and its translation from in vitro , , to ex vivo to in vivo , , , to clinical studies , , . Also, in contrast to the few cell layer‐thick murine periosteum , the ovine femoral periosteal thickness approximates that of humans , .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The robustness of the periosteum is provided by its collagen, while the elasticity of this structure is based on fibers of elastin reinforced by collagenous Sharpey’s fibers anchored to the bone at an angle of 45°. This structural arrangement maintains the periosteal tissue in a state of anisotropic tensional pre-stress ( Knothe Tate et al, 2016 ). Changes in this stress following bone fracture and periosteal lesion leads to deformation of the structural collagen fibrils and cellular nuclei, as well as rapid emigration of cells ( Yu et al, 2017 ).…”
Section: The Periosteal Stem Cell Nichementioning
confidence: 99%
“…Such observations have led to the proposal that the periosteal tissue acts as a mechanosensor and it is assumed that the normal state of stress promotes quiescence in the periosteal stem cell niche ( Knothe Tate et al, 2016 ; Yu et al, 2017 ). Theoretically, this quiescence could be achieved through the action of different proteins such as periostin ( Postn ) on per-SSPCs.…”
Section: The Periosteal Stem Cell Nichementioning
confidence: 99%